PENANAMAN NILAI-NILAI PENDIDIKAN ISLAM KEPADA MARQI DALAM EFEKTIVITAS RUQYAH ASWAJA - Solikhin -; Arifin Shiddiq; Lutfan Muntaqo (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2020)
This research is motivated by the existence of data in the form of information in the community, namely; many people assume that ruqyah is synonymous with trance, there is still a sense of worry or fear if ruqyah will experience unconsciousness and thrashing, people's ignorance of the right method of doing ruqyah and not knowing the values of Islamic education that exist in effectiveness ruqyah. Based on this background, what will be discussed are (1) how are the values of Islamic education in the teachings of the marqi faith in the effectiveness of ruqyah? (2) how are the values of Islamic education in the teachings of marqi worship in the effectiveness of ruqyah in the Lembah Giri team, Banjarnegara branch? (3) how are the values of Islamic education in the social teachings of marqi in the effectiveness of ruqyah? From this study it was concluded that in the effectiveness of ruqyah there is a process of instilling faith values and worship values as well as social values, after the effectiveness of ruqyah the worship spirit of marqi and roqi increases. The need for follow-up ruqyah after the effectiveness of the initial ruqyah is carried out.